This divided land: An examination of regional inequalities in exposure to brownfield land and the association with morbidity and mortality in England. (July 2015) - Bambra, Clare; Cairns, Joanne Marie; Kasim, Adetayo; Smith, Joe; Robertson, Steve; Copeland, Alison; Johnson, Karen
Abstract: This paper is the first empirical examination of the association between brownfield land and spatial inequalities in health. Linear mixed modelling of ward-level data suggests that there is higher exposure and susceptibility to brownfield land in the Northern compared to the Southern regions (with the exception of London); that brownfield exposure has an association with regional inequalities in mortality and morbidity within regions (particularly in the North West); that brownfield has an association with inequalities between regions (particularly between the North West and the South East); but that brownfield land only makes a small independent contribution to the North–South health divide in England. However, brownfield land could be a potentially important and previously overlooked independent environmental determinant of spatial inequalities in health in England.